Evidence that dengue virus envelope protein in patient platelets originates from infection of megakaryocytic precursors - Marcos Alvarado Silva; Tannya Karen Castro Jimenez; Edwin Antonio Lopez Kelly; Nallely Diaz Lima; José Alberto San Juan Luis; Diego Sait Cruz Hernández; Sergio Roberto Aguilar Ruiz; José Bustos Arriaga (PLoS ONE, 2026)
Dengue virus infection is a major global health problem with clinical outcomes ranging from mild febrile illness to severe disease. Although a reduction in platelet counts is a common feature of dengue, the mechanisms underlying the presence of viral antigens in circulating platelets remain incompletely understood. In this study, we investigated whether infection of megakaryocytic precursors contributes to the generation of platelets carrying dengue virus proteins. Using the human megakaryocytic precursor cell lines K562 and MEG-01 cell lines as in vitro models, we show that reference strains and clinical isolates of dengue virus infect megakaryocytic precursors and modulate their differentiation, as evidenced by increased expression of the differentiation marker CD41 and the production of platelet-like particles. Flow cytometry analysis demonstrated that PLPs released from infected precursors contained precursor-derived PLP-associated dengue virus envelope protein. Correlation analyses revealed significant associations between the extent of precursor infection and both differentiation markers and PLP-associated E protein levels at early time points. Consistent with these findings, dengue virus E protein was detected in platelets from dengue patients, while no statistically significant differences were observed between clinical severity groups, a trend toward higher proportions of E + platelets were observed in patients with dengue with warning signs or severe dengue. Spearman correlation analyses further supported an association between in vitro precursor infection and the generation of E-positive PLPs. In contrast, platelets from healthy donors incubated ex vivo with dengue virus did not acquire E protein, indicating that direct uptake or infection of circulating platelets is inefficient. Together, these results support a model in which infection of megakaryocytic precursors contributes to the generation of platelets carrying dengue virus antigens, suggesting that platelet-associated E protein may reflect bone marrow involvement during dengue infection.